Banco de germoplasma de populações de Astronium urundeuva (M. Allemão) Engl. procedentes do Cerrado e sua importância frente às mudanças climáticas - Corrêa, Aparecida Juliana Martins (Universidade Federal de São Carlos, 2021)
Conserving genetic diversity ensures the variability necessary for environmental adaptation and progress in plant breeding. Since Astronium urundeuva ("aroeira do sertão") is known and exploited due to its wood resistance, therefore, it is necessary to understand its landscape distribution, in order to preserve its germplasm. This thesis' aims were to characterize A. urundeuva populations progenies, distributed in distinct regions, and to verify their survival upon climatic fluctuations. Progenies from three populations, installed in Selvíria-MS, were evaluatad for growth and reproductive variables, at different ages, measured in 2019. Region climatic data (temperature (T), precipitation (P), evapotranspiration (Eto) and water available (H2Od), averages and accumulated) were also evaluated, between 1996 and 2018. When necessary, data were standardized in Z statistics. Genetic parameters 〖(σ〗^2,h^2,CVs) were obtained from models efficiency, with covariate or not, in order to identify competition between individuals. Sex ratio was determined by flowering in 2019. Best progenies were determined by overlapping generations, and the correlation between aditive (a) and dominance (d) effects was also made. Descriptive (historical) and sequential water balances (from 2018) were made. Relationship between silvicultural and climatic variables was performed using multiple linear regression (RLM). Models with covariates were not efficient. There is an inbalance in sex ratio for progeny tests (1♀:2♂), related to spatial distribution, species characteristics and sexual selection. Few mothers (1-3 per test) were superior to progenies, indicative of few targeted crosses. Significant correlation (S = 0,7375, α < 2,2 * 10-16) between a and d, implies collecting seeds and propagules, with genetic gains in both strategies. Water deficit (m ̂=-12,7 mm) is standard for the region, in all evaluated years. There was a significant correlation between silvicultural variables and Eto (r = -0,745, α < 0,01); bewteen climatic ones, to those related to H2Od (r = 0,464, α < 0,001), which highlights water importance for the species. RLM showed Etom is directly and inversely related to silvicultural variables (rlm = 0,00426, α < 0,001) , and shows the relation between water availability and productivity. Even though it is not a typical Cerrado species, A. urundeuva may have adapted to its conditions, with slow growth during water deficit, to survive, despite water stress periods, showing itself to be long-living over the time. Even so, there is few literature referring to climate impacts on the species, which justifies further studies on this subject.
Germplasm bank of Astronium urundeuva (M. Allemão) Engl. populations from Cerrado and their importance due to climatic changes
Keywords: Aroeira; Água; Evapotranspiração; Seleção; Variabilidade; Evapotranspiration; Selection; Variability; Water; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL